Avaliação da influência de adjuvantes de secagem sobre as propriedades de suco de caju atomizado - Oliveira, Mirela Araújo de (2008)
The fruit industries have been compelled to adapt to the increasing consumer requeriments related to convenience, food safety and health benefits. An evidence of such changes is the increasing production of fruit juices and related products. Although the ready-to-drink fruit nectars are convenience products, they have high weight and volume, since they have water as their main component. This is an inconvenient aspect, and increases transportation costs. The powder juices have some advantages over whole juices, such as easier and cheaper transportation and higher microbial stability. However, the consumers seem to confuse powder juices with the more commonly found fruit-flavored powder drinks, impairing the consolidation of the former in the market. Cashew (Anacardium occidentale) is a fruit from Brazilian Northeast, having great socio-economic importance for that region. It contains the cashew nut (the real fruit) and the cashew apple (pseudofruit). The low stability of the fresh cashew apple has motivated the development of processes to obtain more shelf-stable products which could be available all year long, and at the same time easy to transport to distant markets. Spray drying is the most used technique to dry liquid foods. However, sugar-rich foods such as fruit juices are difficult to dry, since they produce too hygroscopic powders, which are prone to caking and flowing problems. This can be minimized by addition of drying-aids, such as maltodextrins, which reduce their hygroscopicity. The present study involved an attempt to totally or partially replace maltodextrins (MD) by cashew tree gum (CTG), a polysaccharide similar to gum arabic, very abundant in Brazilian Northeast but under-utilized. The objective of the work was to evaluate the impact of two variables – drying aid/cashew apple solids (DA/CA) ratio (2:1-5:1) and degree of replacement of MD with CTG (0-100%), according to a central composite design – on ascorbic acid retention, physical properties (hygroscopicity and flowability) and solubility of spray dried cashew apple juice. The ascorbic acid retention was favored by higher DA/CA ratios and higher replacements of MD. Cashew tree gum was shown as a promising drying aid material. The most adequate drying conditions were considered as being the following: DA/CA ratio, 5:1, with CTG replacing MD in at least 50%.